2019
DOI: 10.1136/bmjopen-2019-029930
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy decisions after fetal or perinatal death: systematic review of qualitative research

Abstract: ObjectivesTo synthesise the findings of qualitative research exploring parents’ experiences, views and decisions about becoming pregnant following a perinatal death or fetal loss.DesignSystematic review and meta-synthesis of qualitative research.Data sourcesMedline, Web of Science, CINAHL, PsycINFO, ASSIA, Embase, PUBMED, Scopus and Google Scholar.Eligibility criteriaNine electronic databases were searched using predefined search terms. Articles published in English, in peer-reviewed journals, using qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…PD has repercussions in subsequent pregnancies [60], which is a complex situation that requires health professionals' support [61]. In some studies, mothers and fathers expressed that a new pregnancy would decrease their pain and emotional emptiness [19,62].…”
Section: Discussionmentioning
confidence: 99%
“…PD has repercussions in subsequent pregnancies [60], which is a complex situation that requires health professionals' support [61]. In some studies, mothers and fathers expressed that a new pregnancy would decrease their pain and emotional emptiness [19,62].…”
Section: Discussionmentioning
confidence: 99%
“…Each qualitative study was assessed using the 2018 Critical Appraisal Skills Programme (CASP) checklist for qualitative research (CASP, 2018). To assess overall study quality, a quality score was calculated by assigning numerical values to each response option (yes = 2, cannot tell = 1, no = 0), and summing across the individual CASP questions, with a maximum possible score of 20 (Dyer et al, 2019). Critical appraisal of the papers according to the CASP checklist identified several gaps in the quality of the papers overall (supporting information Table S2).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Planning pregnancy after death is complex and varies between individuals and sometimes within couples. Dyer et al (2019) reported the descriptive themes included deciding about subsequent pregnancy, diversity of reactions to the event, social network influences, and planning or timing of subsequent pregnancy.…”
Section: Special Care For Women Who Lost Their Babiesmentioning
confidence: 99%